The Effect of Water Activity on the Growth of Aspergillus flavus - Laras Setyowati; Nijma Nurfadila; Arika Purnawati (Future Science, 2023)
Aspergillus flavus is recognized as one of the fungi responsible for inducing diseases and causing damage to both food and feed commodities. This fungus is capable of producing mycotoxins that possess toxic attributes to both humans and animals. The contamination by A. flavus spans a broad spectrum, commencing from field cultivation and extending to storage facilities. One alternative approach to manage this fungus involves the modification of its growth environment. Microorganisms inherently possess a minimum water activity (aw) value crucial for their metabolic processes. The objective of this study is to modify the aw value to inhibit the growth of A. flavus. This research was conducted in vitro using PDA media supplemented with glycerol and distilled water to establish aw conditions of 0.90, 0.92, 0.95, and 0.97. On the seventh day after incubation, the results demonstrated that for 0.90 aw exhibited a significant inhibition on A. flavus growth, with an average colony diameter is 1.34 mm, followed by 0.92 is 1.54 then 0.95 is 1.83 mm, and 0.97 is 1.84 mm. Conversely, treatments with 0.90 displayed the lowest inhibitions (1.34 mm) and 0.97 displayed the highest (1.84 mm). All modified water activity treatments exerted an impact on the growth of A. flavus. As the aw value decreases, the growth of A. flavus becomes increasingly constrained.